The Assistance for Learning English Vocabulary Using Finger Puppets - Hesty Widiastuty Widiastuty; Sri Normuliati Normuliati; Yunus Firmansah Firmansah; Siska Indriyani Indriyani; Nur Melani Yuliana Yuliana (Universitas Bengkulu, 2024)
In teaching the language, they need effective media. It can improve the ability of learners to learnability. In addition, using media can make learning more interesting and exciting, resulting in better material retention. These finger puppets can be an alternative medium in language learning. In addition, finger puppets are perfect for educational games because they are easier to move according to the storyline and increase vocabulary. The purpose of this community service activity is to introduce the use of finger puppets as a medium in vocabulary learning. The vocabulary used is based on the folklore used entitled,